Correction to the Buprestidae and Schizopodidae (Coleoptera) listings from Nomina Insecta Nearctica (1996) - Bellamy, C. L.; Westcott, R. L. (Zootaxa, 2003)
The errors and omissions from the Nomina Insecta Nearctica listings of Buprestidae and Schizopodidae (Insecta: Coleoptera) are corrected. New information is presented for some listings based on taxonomic or nomenclatural changes made after the cut-off date (June, 1994) for that work.